Absolute configuration of resveratrol oligomer glucosides isolated from the leaves of Upuna borneensis. (June 2017) - Ito, Tetsuro; Ito, Hiromi; Iinuma, Munekazu
Graphical abstract: Highlights: Resveratrol oligomers was isolated from Upuna borneensis . Absolute configurations were determined based on NMR and CD spectral properties. Occurrence of O -glucosides bearing an epimeric aglycone of resveratrol pentamers were exhibited. Abstract: A comprehensive investigation of the chemical constituents of the leaves of Upuna borneensis (Dipterocarpaceae) was performed. Three new glucosides of resveratrol oligomers having a pentameric aglycone [upunoside E (1 )] and dimeric aglycones [upunosides F (3 ) and G (4 )], as well as 14 resveratrol derivatives (2, 5 –17 ), were isolated. The absolute configurations of the new compounds were elucidated by spectroscopic analysis, including two-dimensional NMR and CD spectra.